Reactivity pattern of in situ generated tetraethylammoniun superoxide with some flavonoids - Singh K.N.; Kumar R. (My University, 2025)
A number of flavonoids have been allowed to react under the mild reaction conditions of tetraethylammonium superoxide in dry dimethylformamide at room temperature. As an outcome, 3-hydroxyflavones 1a-c undergo oxidative ring cleavage to afford 2-benzoyloxyphenylglyoxylic acids 2a-c, whereas the substrates 1d-f result in the formation of acids 2d-f alongwith 3d-f.